Application of numerical models to evaluate oil spills propagation in the coastal environment of the Black Sea - Rusu, Liliana (Journal of Environmental Engineering and Landscape Management, 2010)
The last decades continuously increasing of the economical activities in the coastal environment of the Black Sea is obviously leading to the enhancement of the pollution risks due to accidental oil spillages. Starting from the fact that most accidents were generated by an inadequate forecast of the wave conditions, the aim of the present work is to develop a methodology based on spectral phase–averaging wave models able to predict the wave propagation in the coastal environment. The wave induced currents that may be a key factor in driving the pollution are also assessed. This implies both the Stokes drift and the wave induced nearshore currents. The surface streaming effect due to the molecular viscosity was also accounted for. In the nearshore, close to the surf zone, the pollution is usually spread along the coast due to the longshore currents. In this connection, the results of a simple but effective model system called ISSM are also presented. As an alternative simulations with the SHORECIRC model system are also performed. Finally, as a case study, the propagation of the pollution towards the Romanian coast generated by a hypothetic accident at the Gloria drilling platform was assessed.Article in English.Skaitinių modelių taikymas vertinant išsiliejusios naftos pasklidimą Juodosios jūros priekrantės zonojeSantrauka. Per pastaruosius dešimtmečius plėtojant pramonę Juodosios jūros priekrantės zonoje, dėl atsitiktinių naftos išsiliejimų padidėjo taršos rizika. Viena iš priežasčių, dėl kurių įvyksta tokios avarijos, yra netikslios bangų būkles prognozės. Darbo tikslas – remiantis spektrinių fazės vidurkių apskaičiavimų modeliais, sukurti metodologiją, kuri leistų numatyti bangų sklidimą priekrantės zonoje. Taip pat įvertinamos bangos sukeltos srovės. Jos gali būti vienas iš pagrindinių veiksnių, turinčių įtakos teršalų sklidimui jūroje. Į skaičiavimus įtraukiama Stokso tėkmė bei bangos sukeltos pakrantės srovės, išreiškiamas paviršiaus srovių efektas pagal molekulinę klampą. Dėl ilgųjų pakrantės srovių prie kranto iš arčiau paviršiaus zonos esančio šaltinio tarša dažniausiai sklinda palei pakrantę, todėl rezultatai pristatomi taikant modeliavimo sistemas ISSM ir SHORECIRC. Modeliuojant remtasi studija, kurioje vertinamas taršos sklidimas ties Rumunijos pakrantės dėl spėjamai įvykusios avarijos Glorijos gręžinio platformoje.Reikšminiai žodžiai: ekologinis įspėjimas, naftos išsiliejimai, bangos, bangos sukeltos srovės, skaitiniai modeliai, Juodoji jūra.Использование численных моделей для оценки распространения разлива нефти в прибрежной зоне Чёрного моряРезюме. Постоянно увеличивающаяся в последние десятилетия экономическая активность в прибрежной зоне Чёрного моря ведёт к большему риску загрязнения из-за случайных разливов нефти. В связи с тем, что большая часть случаев разлива была связана с неадекватным прогнозом волнения, целью настоящей работы было разработать методологию, основанную на спектральных моделях волнения с усреднением фазы, способную предсказывать распространение волн в прибрежной зоне. Было оценено также течение, вызванное волнением, которое может стать решающим фактором в распространении загрязнения. Оно включает в себя стоксовое дрейфовое течение и прибрежное течение. Учтено также поверхностное течение, вызываемое ветром через касательные напряжения. В качестве примера рассмотрено распространение в направлении румынского берега загрязнения, вызванного гипотетической аварией на буровой платформе Глория.Ключевые слова: экологическое предупреждение, разливы нефти, волны, течения, вызываемые волной, численные модели, Чёрное море.First Publish Online: 10 Feb 2011